Variasi Morfometrik Kodok Duttaphrynus melanostictus (Schneider, 1799) (Anura: Bufonidae) di Sumatera Barat yang Dipisahkan oleh Bukit Barisan - Ravelino Nesty; Djong Hon Tjong; Henny Herwina (Universitas Andalas, 2013)
The research on morphometric variations of toads Duttaphrynus melanostictus (Schneider, 1799) (Anura: Bufonidae) in West Sumatera those separated geographically by Barisan Mountain was conducted from July to September 2012 with 4 sampling areas (Surantih, Padang, Suliki and Sijunjung). Survey and direct collection methods were used in this study. Morphometric characters measurement was conducted at Animal Taxonomy Laboratory of Biology Department, Faculty of Sciences, Andalas University. The purpose of this study was to determine the morphometric variation in population of D. melanostictus. The results showed that morphometric differentiation between western and eastern population of D. melanostictus in both within males and females. This finding might support that Barisan Mountain has isolated the populations.Keywords: morphometrics, variation, Duttaphrynus melanostictus, West Sumatra